2012
DOI: 10.1002/ece3.233
|View full text |Cite
|
Sign up to set email alerts
|

Gene or environment? Species‐specific control of stomatal density and length

Abstract: Stomatal characteristics are used as proxies of paleo-environment. Only a few model species have been used to study the mechanisms of genetic and environmental effects on stomatal initiation. Variation among species has not been quantified. In this paper, results from an in situ reciprocal transplant experiment along an elevation gradient in the northeast Tibetan Plateau are reported, in which the relative effects of genetics (original altitude) and environment (transplant altitude) on stomatal density (SD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
2
37
3
Order By: Relevance
“…only trait that contribute to population differentiation are pore length (PL) and shape (PSC). Length is considered to be under strong genetic control and less under environmental influence (Zhang et al 2012). However, stomatal density (SD), which is considered as a genetically determined quantitative trait (Gailing et al 2008), did not show significant differences (P = 0.8884) in this study.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…only trait that contribute to population differentiation are pore length (PL) and shape (PSC). Length is considered to be under strong genetic control and less under environmental influence (Zhang et al 2012). However, stomatal density (SD), which is considered as a genetically determined quantitative trait (Gailing et al 2008), did not show significant differences (P = 0.8884) in this study.…”
Section: Discussioncontrasting
confidence: 58%
“…Stomata are the apertures found on the surface of leaves, flanked by guard cells, which regulate the gas exchange between the internal plant tissue and the atmosphere, especially water vapor and CO 2 (Zhang et al 2012,), and the environment, allowing the plant to optimize and balance the photosynthetic performance with water availa-bility and usage (Chaerle et al 2005). The gas exchange regulation is achieved not only through the actual opening and closing of the stomatal pore, but by either increasing or reducing the stomatal conductance (Casson and Gray 2008), as well as by the number and size of stomata on leaf surfaces (Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genetic factors might be responsible for the observed differences in stomatal responses to historic climate change (Casson & Hetherington, ). The stomatal characteristics of some species show high heritability (less sensitivity to environmental changes), whereas those of other species are more sensitive to environmental factors (Schoch et al ., ; Zhang et al ., ; Tanaka et al ., ). We found that the SD responses to climate change differed among different life forms (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic and hormonal manipulation of stomatal density in flowering plants (Tal et al, 1970;M artin & Stimart, 2005;Doheny-Adams et al, 2012;Zhang et al, 2012), together with investigations into the effects of carbon dioxide concentrations (McElwain & Chaloner, 1995;W oodward & Kelly, 1995;Beerling, 2007;Konrad et a l, 2008), are at the forefront of current research on yield improvement and climate change. Alongside these experimental studies a wide variety of stomatal defects, affecting both guard cell and subsidiary cell morphology and vitality, have been reported from numerous vascular plants (Dehne, 1961;Takahashi, 1962;Inam dar & Patel, 1969;Inamdar et a l, 1969;Gopal & Shah, 1970;Inam dar et a l, 1970;Inam dar & Patel, 1976).…”
Section: Introductionmentioning
confidence: 99%